Grades of brain arteriovenous malformations and risk of hemorrhage and death - Stefani, Marco A. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To assess the relationship of the grade of unruptured and untreated Brain Arteriovenous Malformations (AVMs), with the risk of subsequent stroke and death during follow‐up. METHODS: This prospective study was drawn from a cohort of adult patients with unruptured AVMs, who participated in the conservative treatment arm (medical management only for headache or seizures) of the randomized clinical trial of unruptured brain AVMs (ARUBA study). The grade of AVMs (Spetzler–Martin scale) was dichotomized into categories: AVMs of grades I and II were considered low grade; AVMs of grades III and IV were considered high grade. There were no grade V AVM patients in ARUBA. The primary outcome was symptomatic stroke (hemorrhagic or ischemic – documented by imaging) or death. RESULTS: The conservative treatment group had 123 patients (“as treated” analysis). 71 (57.7%) had lesions characterized for this analysis as low‐grade lesions and 52 (42.2%) as high grade. From the total of 10 (8.13%) primary outcomes, three occurred (4.22%) in low‐grade AVMs and seven (13.46%) in high‐grade AVMs (P = 0.0942). INTERPRETATION: Statistical analysis of the cohort of patients with unruptured and untreated AVMs from ARUBA study showed that the graduation categories (Spetzler–Martin grades) were not associated with the outcome of subsequent stroke or death.